An exploration into student learning mobility in higher education among the Arabian Gulf Cooperation Council countries. (July 2017) - David, S.A.; Taleb, H.; Scatolini, S.S.; Al-Qallaf, A.; Al-Shammari, H.S; George, M.A.
Abstract: This paper explores the dynamics of the internationalisation of higher education in the Gulf region. Exploring the presence of foreign universities, international curricula, programmes, students and academic staff, it pays particular attention to the learning mobility of students from the region. Consequently, the aim of this piece of research is to explore the current learning mobility among the GCC countries. The study makes use of secondary data from the UNESCO Institute for Statistics (UIS) on the global flow of tertiary-level students and a survey conducted especially for this study among students from the Gulf region. Considering the literature explored and based on data from UIS and the survey conducted, it seems that higher education in the Gulf region has expanded and that the presence of foreign universities, international curricula, programmes, students and academic staff is a positive experience overall. Although learning mobility has been stimulated in the region, much of it is regionally driven. It seems that the growth of inward learning mobility is not proportional to the growth of foreign universities in the region. The growth of outward learning mobility is predominantly driven by scholarships and the potential for growth on inward and outward learning mobility seems likely to increase in the future. The Gulf countries may enhance learning mobility through multilateral learning and research cooperation by means of scholarships and regulated commercial activities. To emerge as an international education hub, the Gulf countries must become an attractive destination for students from outside of the region as well. The region may wish to draw relevant lessons from regions such as the European Union to stimulate learning mobility.